THE QUEST FOR ROBUST ENFORCEMENT OF THE LAW ON TRADEMARKS IN UGANDA TO MAXIMIZE ITS ECONOMIC BENEFITS. A SYSTEMATIC REVIEW. - Nyamwija , Mary; Butagira K., Francis; Mugarura, Norman (Student's Journal of Health Research Africa, 2024)
Introduction With ever-increasing cases of trademark counterfeiting and infringement globally due to sophisticated technological advancements, it has become imperative for companies to register their trademarks to enjoy the benefits that accrue from their registration. Not only has registration of trademarks benefited trademark owners, but it is also a means of technological transfer between states and a source of government revenue. In this study, the law on trademark enforcement was examined in a quest for robust enforcement mechanisms to maximize the economic benefits. Purpose: This study analyzed the law on trademark enforcement in Uganda in a quest for robust enforcement mechanisms to maximize the economic benefits. It involved a probe into the adequacy of the existing legal and institutional framework on trademark enforcement mechanisms since it is a necessity to any given country irrespective of its level of economic development. It not only enhances the protection of the existing trademark rights but also encourages creators and investors to settle in an environment that is conducive to creativity and investment. Methodology The study utilized doctrinal research methodology, analyzing data from authoritative sources like statutes, conventions, and judicial decisions, and utilizing content analysis techniques for clear and concise answers. Results The study revealed that Uganda has a robust legal and institutional framework for trademark enforcement though with weak penalties. The institutional framework is weak, lacking sufficient funds and trained personnel to effectively deter counterfeiting and infringement. Conclusion The empirical literature indicates that Uganda has a robust legal framework for trademark enforcement but the penalties are insufficient to deter counterfeiting and infringement. Recommendations The authors recommended the amendment of the Trademarks Act to provide sentences that are deterrent in nature, promotion of public awareness, and training of the required personnel.